Psychometric characteristics of the deductive thinking test in the light of the paragraph response theory for high school female students in Makkah Al-Mukarramah - Basakran, Faizah Ahmed Mohammed (Journal of Educational and Psychological Sciences, 2023)
The current study aimed to reveal the psychometric characteristics of the deductive thinking test according to its dimensions reasoning (Numerical, Verbal, numerical and verbal, General deduction, General induction) in the light of the paragraph response theory, and The research relied on the descriptive survey method, and it was applied to an intended sample of secondary school students in Makkah consisting of (1010) students, and the WINSTEPS program was used to verify the assumptions of the theory of response to the test paragraph (One-Dimensional- Positional Independence- Freedom from Speed) in the deductive thinking scale. The inferential reasoning scale showed an appropriate degree of validity represented in the validity of the test construction, the validity of the gradient, and the validity of the variable definition. as the items’ stability coefficient was (0.99), and the value of the individuals’ stability coefficients was (0.84). The information function of the deductive thinking test also provided a large amount of information, The study of the differences between Female students resulted in the presence of statistically significant differences between female students in the study sample in deductive thinking due to the variable of the student’s specialization (scientific/ literary) in favor of female students of literary specialization with a weak effect size(0.022). and Depending on the variable the variable of the academic grade (second/ third) in favor of third grade female students with a weak effect size(0.008). The study concluded by using the test in its final form consisting of (32) items to measure the inferential thinking of female students at different educational levels, and the use of standardized tests such as the inferential thinking test in the light of the response theory in educational studies and research more than others.